COLLECTIVE ACTION AND ASPIRATIONS: THE IMPACT OF COOPERATIVES ON ETHIOPIAN COFFEE FARMERS' ASPIRATIONS. (18th December 2015) - MOJO, Dagne; FISCHER, Christian; DEGEFA, Terefe
ABSTRACT: Aspirations motivate behaviours, serve to mobilize and direct energy into actions, and are regarded as important determinants of success. Given the importance of aspirations and their formation in social interaction, the objective of this article is to evaluate if cooperative membership can have effects on members' aspiration levels. Face‐to‐face interviews were conducted with 305 Ethiopian coffee farmers on their aspired levels in five dimensions of their lives. Results, using a propensity score matching technique, show that membership in cooperatives significantly improves the aspiration levels of the members. The article emphasizes the utilization of this hidden but important benefit of cooperatives.